Five Clinical Cases of Facial Chuna Manual Therapy with Korean Medicine Treatment for Acute Bell's Palsy - Jung Min Son; Hye Soo Youn; Eun Chang Lee; Choong Hyun Park; Sun Woo Kwon; Ji Yoon Lee; Da Young Han; Haeni Seo (MEDrang Inc., 2023)
This study individually analyzed the effects of Korean Facial Chuna Manual Treatment (K-FCMT) combined with Korean medicine (KM) treatment (acupuncture, electroacupuncture, pharmacopuncture, and herbal medicine) on five patients with acute Bell's palsy who visited Dongsuwon Korean Medicine Hospital between August 1 and 31, 2022. During inpatient treatment, two of the five patients received K-FCMT 5-6 times a week, and the other three received the same frequency during outpatient treatment for approximately 2 weeks. Patients with a House-Brackmann grading scale (HBGS) score of ≤4 and Yanagihara unweighted grading system (Y-score) ≥7-8 began to recover after the 2nd-3rd sessions of K-FCMT, which entered the recovery phase quickly. As patients entered the recovery phase (7-9th sessions of K-FCMT), symptoms improved to HBGS scores of 1-2 and Y-scores of 35-40 points. This study suggests the possibility of applying K-FCMT combined with KM treatment to patients in the acute stage of Bell's palsy.